Validation of spatial microsimulation models: a proposal to adopt the Bland-Altman method - Timmins, Kate A.; Edwards, Kimberley L. (International Microsimulation Association, 2016)
Model validation is recognised as crucial to microsimulation modelling. However, modellers encounter difficulty in choosing the most meaningful methods to compare simulated and actual values. The aim of this paper is to introduce and demonstrate a method employed widely in healthcare calibration studies.